Remittances and Trade Deficit in Nepal: A VECM Analysis of Long-Run and Short-Run Dynamics - Ojha, Radhika (NPRC Journal of Multidisciplinary Research, 2026)
Background: Remittances constitute a vital source of foreign exchange for Nepal, accounting for 25–30 percent of GDP. Despite substantial inflows, the country continues to experience a persistent and widening trade deficit, presenting a paradox that warrants empirical investigation. Objective: This study examines the long-run and short-run dynamics between remittance inflows, merchandise imports, and the merchandise trade deficit in Nepal, addressing three key questions: the long-run relationship between remittances and imports; the long-run and short-run relationship between remittances and the trade deficit; and the adjustment mechanisms toward equilibrium. Methods: Using annual time-series data from 1990 to 2022, the study employs the Johansen cointegration test and Vector Error Correction Model (VECM) to capture both short-run dynamics and long-run equilibrium relationships. All variables were transformed into natural logarithms and tested for stationarity using the Augmented Dickey–Fuller test. Findings: Results reveal that all variables are integrated of order one. A 1 percent increase in remittances leads to approximately a 1.05 percent increase in imports in the long run, indicating substantial import leakage. Remittances exhibit opposing effects on the trade deficit: a slight short-run reduction (−0.0357%) followed by a long-run widening (+0.0587%). Diagnostic tests confirm model reliability with no serial correlation or heteroskedasticity. Conclusion: The findings provide indirect evidence of Dutch Disease effects, where remittance inflows appreciate the real exchange rate, making exports less competitive while stimulating import demand. Policy recommendations include enhancing domestic absorptive capacity, encouraging productive investment of remittances, and integrating remittance policies with broader development planning. Novelty: This study contributes to the literature by using the most recent data (1990–2022), employing VECM to capture both short-run and long-run dynamics, separately analyzing remittances–imports and remittances–trade deficit relationships, and providing updated policy recommendations tailored to Nepal’s current economic context.